Climate Change Characteristics of Coastal Wind Energy Resources in Zhejiang Province Based on ERA-Interim Data - Wang, Nan; Zhou, Kai-Peng; Wang, Kuo; Feng, Tao; Zhang, Yu-Hui; Song, Chao-Hui (Frontiers in Physics, 2021)
The reanalysis of sea surface wind speed is compared with the measured wind speed of 5 offshore wind towers in Zhejiang, China. The applicability of reanalysis data in Zhejiang coastal sea surface and the climatic characteristics of sea surface wind power density are analyzed. Results show that the reanalysis of wind field data at the height of 10m can well capture the wind field characteristics of the actual sea surface wind field. The sea surface wind power density effective hours increases from west to east and north to south. Then Empirical orthogonal function(EOF) is used to analysis the sea surface wind power density anomaly field, and the first mode is consistent pattern, the second mode is North-South dipole pattern, the third mode is East-West dipole pattern respectively; The stability of wind energy resources is more stable with increasing distance from coast, and the northern sea area which is far away from coast sea is more stable than that of the southern sea area. The yearly linear trend of sea surface wind power density is East-West dipole pattern respectively. The wind energy resources is more stable farther from coast, and the wind energy resources in northern sea is more stable than that of the southern sea. The yearly linear trend of sea surface wind power density is the East-West dipole type, the seasonal linear trend is significant downward trend from West to East in spring, and on the contrary in summer, non-significant trend in autumn and winter. The monthly change index shows that the linear trend near the entrance of Hangzhou Bay in Northern Zhejiang is weak increase or decrease which is good for wind energy development.When the wind power density is between 0 to 150 W·m-2, its frequency mainly shows the distribution trend of high in the West and low in the East, but the wind power density is between 150 to 600 W·m-2, its distribution is just the opposite.